2019
DOI: 10.1186/s13099-019-0286-9
|View full text |Cite
|
Sign up to set email alerts
|

CagL polymorphisms D58/K59 are predominant in Helicobacter pylori strains isolated from Mexican patients with chronic gastritis

Abstract: Background: Helicobacter pylori is a Gram-negative bacterium that colonizes the gastric mucosa in humans. One of the main virulence factors of H. pylori is the cag pathogenicity island (cagPAI), which encodes a type 4-secretion system (T4SS) and the cytotoxin CagA. Translocation of CagA through the T4SS triggers host-signaling pathways. One of the T4SS proteins is CagL, which is necessary for CagA translocation. CagL is a 26-kDa protein that contains a hypervariable motif, which spans residues 58 to 62. Severa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 44 publications
0
16
1
Order By: Relevance
“…More recent sequencing studies have identified a number of variants in this gene. The other cagL variant associated with GC in our study, on residue 134, has been reported with variable results in other studies in Latin America 34,36,37 ; although this variant has not been detected in East Asian strains 33,35 . Thus, although the data from these Western strains are inconclusive in terms of its association with GC, this cagL variant is likely to represent a Western strain‐specific marker.…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…More recent sequencing studies have identified a number of variants in this gene. The other cagL variant associated with GC in our study, on residue 134, has been reported with variable results in other studies in Latin America 34,36,37 ; although this variant has not been detected in East Asian strains 33,35 . Thus, although the data from these Western strains are inconclusive in terms of its association with GC, this cagL variant is likely to represent a Western strain‐specific marker.…”
Section: Discussioncontrasting
confidence: 54%
“…To date, Hp genotyping on biopsy specimens has been almost limited to CagA EPIYA motif patterns 32 . There are more recent studies based on sequencing technology, reporting associations between specific Hp genetic variants and clinical phenotypes 33‐37 . However, these sequencing studies have been performed on a limited number of samples and with Hp strains isolated from the patients.…”
Section: Discussionmentioning
confidence: 99%
“…This RGD-dependent binding of CagL to integrins was also shown to trigger intracellular signaling pathways inducing cell pro-inflammatory responses that are CagA translocation-independent [46,137,138]. Recent studies found an association of novel CagL variants with chronic gastritis and peptic ulcer disease (PUD) development [139,140]. Particular polymorphisms upstream of the RGD motif at amino acid residues 58–62, called the CagL hypervariable motif (CagLHM), are correlated with severe disease progression in a geographically-dependent manner [141,142].…”
Section: Virulence Factors Associated With Gastric Epithelial Cellmentioning
confidence: 99%
“…These included Chile (15.2%) and Malaysia (43.0%) (24,33) . The different rate of detection of the cagA gene can possibly be attributed to the genetic polymorphism, characteristics of different H. pylori strains, as well as the different rates of prevalence of infection in these countries (34) .…”
Section: Discussionmentioning
confidence: 99%